A Study of Ocular Manifestations in Pregnancy Induced Hypertension in a Tertiary Healthcare Centre - Reshma, Ramakrishnan A.; Priyanka, Gandhi H.; Abha, Shah; Saloni, Pugalia (British Journal of Healthcare and Medical Research, 2022)
Pregnancy Induced Hypertension (PIH) is a perplexing taint in the obstetrics field. Visual symptoms occur in up to 25% of these patients. Ocular manifestations include blurring of vision, sudden inability to focus, photopsia,etc. Aim: To determine the ocular manifestations of PIH, create awareness and promote the need of ophthalmic consult for early diagnosis and optimum feto-maternal care in these patients. Settings and Design: A cross‐sectional study was done by recruiting PIH patients admitted in Obstetrics and Gynaecology department as the subjects, after obtaining ethical approval from the institute and informed consent from the patients. Methods: 100 PIH patients aged 18-35 years who were admitted in Obstetrics and Gynaecology department over a period of 3 months were included in this study. Detailed ophthalmic examination was done and findings recorded. Statistical Package for Social Sciences (SPSS V 26.0, IBM) was used for statistical analysis. P value <0.05 was considered significant. Results: Twenty six(26%)patients had previous history of PIH. Chloasma was seen in eight(8%) patients. 32(32%) patients experienced blurring of vision. Anaemic retinopathy was seen in six patients(6%), grade I hypertensive retinopathy changes were seen in nine patients(9%), grade II hypertensive retinopathy changes were seen in four patients(4%), early papilloedema was seen in one patient(1%) and early Vogt-Koyanagi- Harada disease was seen in one patient(1%). Conclusion: Patient counselling and regular ophthalmic consults are necessary for allaying fears and providing optimum visual care to these patients.